A review on larvicidal and repellent effects of Brassica nigra towards malaria mosquito - Bekele, Damtew (Journal of Medicine and Health Sciences Research, 2023)
The efficacy of synthetic insecticides to control malaria vectors is compromised by increased mosquito resistance to insecticides. Furthermore, the use of inorganic insecticides raises serious environmental toxicity concerns. It is hoped that this review would incorporate plant-based control tools in modern malaria vector control at the community level. Therefore the use of synthetic insecticides is the challenge faced for malaria vector control because of the resistance of mosquitoes and their toxicity to the environment. Medicinal plants used like Brassica nigra in traditional medicine are promising and largely unexplored sources for the development of potential new compounds particularly in plant-rich countries like Ethopia.